A comparative analysis of lean implementations in NHS England hospitals. (2018) - Deara, Adnan; Deara, Mohamed; Bamber, Christopher; Elezi, Enis
The paper investigates and documents the effect of implementing lean in NHS England Hospitals through an evaluation of one quantitative study that questioned a large number of NHS staff and three case study reviews of implantation of lean projects. The purpose of lean implementation in these UK studies has been shown as predominantly to improve times, use staff more effectively, improve quality, decrease waste and reduce cost and smooth arrivals of patient demands. Moreover, lean in the NHS is used to utilise the available resources in the best manner. This paper indicates that most of the barriers which have been identified by 88% of the interviewed people, from the NHS quantitative study, were due to the terminology of new language and consequently poor communications of lean principles. The critical success factors elicited from this study include a widespread commitment of project success and the application effective governance. Setting clear goals, project planning and competent project teams, are considered by respondents and seen in the analysis of the three case studies reviewed in this study; all play an important role in successful NHS lean projects.